1995
DOI: 10.1073/pnas.92.21.9450
|View full text |Cite
|
Sign up to set email alerts
|

Role of the GATA factors Gln3p and Nil1p of Saccharomyces cerevisiae in the expression of nitrogen-regulated genes.

Abstract: We have isolated the NILI gene, whose product is an activator of the transcription of nitrogen-regulated genes, by virtue of the homology of its zinc-finger domain to that of the previously identified activator, the product of GLN3. Disruption of the chromosomal NILI gene enabled us to compare the effects of Gln3p and of Nillp on the expression of the nitrogen-regulated genes GLN1, GDH2, and GAP), coding respectively for glutamine synthetase, NAD-linked glutamate dehydrogenase, and general amino acid permease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
185
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(194 citation statements)
references
References 18 publications
7
185
2
Order By: Relevance
“…GAATAG/GATA-type sequences which are the binding target of the transcription factor Gln3p were also found in the GAP1 promoter of S. cerevisiae (Miller & Magasanik, 1991). TTGGT or TTGTT plays an auxiliary role in activation of nitrogen-regulated genes by Gln3p (Stanbrough et al, 1995). Another transcription factor, Cph1p/Acprp of C. albicans, a homologue of Ste12p of S. cerevisiae, binds to a heptamer sequence, TGAAACA, referred to as a pheromone responsive element (PRE).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GAATAG/GATA-type sequences which are the binding target of the transcription factor Gln3p were also found in the GAP1 promoter of S. cerevisiae (Miller & Magasanik, 1991). TTGGT or TTGTT plays an auxiliary role in activation of nitrogen-regulated genes by Gln3p (Stanbrough et al, 1995). Another transcription factor, Cph1p/Acprp of C. albicans, a homologue of Ste12p of S. cerevisiae, binds to a heptamer sequence, TGAAACA, referred to as a pheromone responsive element (PRE).…”
Section: Resultsmentioning
confidence: 99%
“…proline, the amino acid uptake is high (Blinder et al, 1996;Courchesne et al, 1983). In S. cerevisiae, at least five proteins (Ure2p, Dal80p, Gln3p, Nil1p and Nil2p) function co-ordinately to control the transcription of GAP1 (Blinder et al, 1996;Cunningham et al, 1993;Rowen et al, 1997;Stanbrough et al, 1995). The nitrogendependent regulation of GAP1 is complex, occurring not only at the level of GAP1 transcription but also through Gap1p sorting and degradation by ubiquitin-triggered internalization (Springael et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Several independent reports have shown that nitrogen-repression-sensitive transcription of some genes is not entirely Gln3p-dependent (Coffman et a/., 1995;. More recently, a second GATA factor has been discovered, encoded by the NIL 71 GAT7 gene, which is responsible for this Gln3p-independent, nitrogen-repression-sensitive expression (Stanbrough et a/., 1995;Coffman ef a/., 1996). Transcription of the nitrogen-sensitive GAP1 gene encoding general amino acid permease (Jauniaux and Grenson, 1990) is under the positive control of both Gln3p and Nillp.…”
Section: Introductionmentioning
confidence: 99%
“…In both gln3A and nil7A single mutants, expression of GAP7 remains high on media where the nitrogen source is poor, but it is abolished in the gln3A nil7A double mutant (Stanbrough et a/., 1995;Coffman et al, 1996). Analysis of the single mutants suggested that expression supported by Gln3p alone might be inhibited by high intracellular concentrations of glutamine, Nil1 p-dependent transcription being inhibited by high intracellular glutamate (Stanbrough et a/., 1995). The GATA factor encoded by the UGA431 DALBO gene (Cunningham and Cooper, 1991 ;Coornaert et a/., 1992) was isolated because mutations in this gene cause constitutive expression of inducible genes involved in allantoin (Chilsholm and Cooper, 1982) or y-aminobutyrate (Vissers et a/., 1989) utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in the presence of high-quality nitrogen sources such as glutamine, a decrease in the levels of catabolic enzymes is observed. The reduced expression of the genes coding for enzymes involved in the utilization of poor nitrogen sources is brought about through the action of a regulatory system known as nitrogen catabolite repression (NCR) (Blinder & Magasanik, 1995;Coffman et al, 1995Coffman et al, , 1996Courchesne & Magasanik, 1988;Minehart & Magasanik, 1991) NCR operates through the action of two transcriptional activators, Gln3 and Nil1/ Gat1, and two repressors, Dal80 and Gzf3/Deh1/Nil2 (Minehart & Magasanik, 1991;Stanbrough et al, 1995;Svetlov & Cooper, 1998;Magasanik & Kaiser, 2002), whose expression is regulated by nitrogen levels. In the presence of repressive nitrogen sources, the TOR signalling pathway promotes the association of the GATA transcription factors Gln3 and Gat1 with the cytoplasmic protein Ure2, thus retaining Gln3 and Gat1 in the cytoplasm (Beck & Hall, 1999;Cardenas et al, 1999;Hardwick et al, 1999).…”
Section: Introductionmentioning
confidence: 99%